2017
DOI: 10.1186/s40545-017-0125-7
|View full text |Cite
|
Sign up to set email alerts
|

To what extent do prescribing practices for hypertension in the private sector in Zimbabwe follow the national treatment guidelines? An analysis of insurance medical claims

Abstract: BackgroundHypertension is the most prevalent cardiovascular disease in Zimbabwe. The prevalence of Hypertension in the country is above 30% regardless of the cut off used. Currently, majority of patients in Zimbabwe seek health care from the private sector due to limited government funding for the public health sector. However, Standard treatment guidelines for hypertension are only available in the public sector and are optional in the private sector. This study assesses compliance of private sector prescribi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…ACEI/Angiotensin receptor blockers were the most prescribed agents (63 times), unlike in this study that had diuretics. Only 358 (35%) prescriptions complied with guidelines, which indicates poor compliance [7]. The findings of the study are similar to those found in other countries, as was in the present study [8,9].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…ACEI/Angiotensin receptor blockers were the most prescribed agents (63 times), unlike in this study that had diuretics. Only 358 (35%) prescriptions complied with guidelines, which indicates poor compliance [7]. The findings of the study are similar to those found in other countries, as was in the present study [8,9].…”
Section: Discussionsupporting
confidence: 86%
“…In Zimbabwe, research by Basopo et al (2017) assessed the prescribing practices for hypertensive patients in the private sector to verify whether it followed the national treatment guidelines. The majority of the populace in Zimbabwe seek medical care from the private sector.…”
Section: Discussionmentioning
confidence: 99%
“…Health facility capacity to manage hypertension in the Uganda survey showed the need of additional training on hypertension management by all health workers [ 70 ]. A similar study from Zimbabwe showed that professional knowledge was poor among 47.7% of health workers [ 105 , 106 ]. Another study from Rwanda showed that 43% of clinicians had poor knowledge [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly prescribed antihypertensive medications were ACEIs/ARBs, a prescribing pattern that has been reported in several other studies. [252728] Besides being first-line medications, it has been shown that ACEI/ARB therapy helps to delay or prevent the progression of CKD, and guidelines accordingly emphasize this approach as a compelling indication for patients with CKD or diabetes mellitus without contraindications. [12] More than one-third of this study population were diabetic and this could explain the high trend of ACE/ARB use.…”
Section: Discussionmentioning
confidence: 99%